Los inicios del astillero de la Habana en el siglo XVIII y la influencia francesa (2011)
ABSTRACT: This paper endeavours to discuss French influence at the very beginnings of the rise of the Havana shipyards during the eighteenth century. Although the French influence, with regards to marine issues, has been considered to be somewhat irrelevant by scholars, this paper attempts to show how French ideas were very influential as much within the general scope of the Spanish merchant marine during the eighteenth century, as they were, more specifically, within the Havana shipyards. French reforms, in economic and administrative areas, are key to understanding Havana’s success in marine policy during this time, in spite of the political disputes of the Spanish monarchy.